2011
DOI: 10.1007/s10534-011-9430-9
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology approach to Wilson’s disease

Abstract: Wilson’s disease (WD) is a severe disorder of copper misbalance, which manifests with a wide spectrum of liver pathology and/or neurologic and psychiatric symptoms. WD is caused by mutations in a gene encoding a copper-transporting ATPase ATP7B and is accompanied by accumulation of copper in tissues, especially in the liver. Copper-chelation therapy is available for treatment of WD symptoms and is often successful, however, significant challenges remain with respect to timely diagnostics and treatment of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 69 publications
1
56
0
Order By: Relevance
“…These findings suggest that altered lipid metabolism may be involved in Cu toxicity. Also, using animal models of Wilson’s disease to study gene and protein profiling, Burkhead et al (2011) have revealed the link between molecular players and pathways, including cell cycle and cholesterol metabolism, mRNA splicing and nuclear receptor signaling, and Cu imbalance, and uncovered cellular processes that are primarily affected by Cu accumulation in the liver.…”
Section: Cu Toxicitymentioning
confidence: 99%
“…These findings suggest that altered lipid metabolism may be involved in Cu toxicity. Also, using animal models of Wilson’s disease to study gene and protein profiling, Burkhead et al (2011) have revealed the link between molecular players and pathways, including cell cycle and cholesterol metabolism, mRNA splicing and nuclear receptor signaling, and Cu imbalance, and uncovered cellular processes that are primarily affected by Cu accumulation in the liver.…”
Section: Cu Toxicitymentioning
confidence: 99%
“…Complete functional loss of ATP7B results in severe WD phenotypes in humans (31,32). The Atp7b -/-rat carries an Atp7b mutation that abolishes its hepatic copper transport activity (16,17). These animals rapidly progress from a copper-burdened liver to hepatic failure and death (18).…”
Section: Mitochondrial Impairment Is Pathognomonic For Hepatic Failurmentioning
confidence: 99%
“…We recently described copper-driven fulminant hepatitis in LPP Atp7b -/-rats that carry a homozygous 13-kb deletion in the Atp7b gene (hereafter referred to as Atp7b -/-rats) (16)(17)(18). Because of this recessive genetic defect, heterozygous Atp7b +/-rats have a normal phenotype.…”
Section: Mitochondrial Impairment Is Pathognomonic For Hepatic Failurmentioning
confidence: 99%
“…Wilson disease usually presents in the teenage years or young adulthood with symptoms ranging from neurological dysfunction, chronic liver disease, fulminant hepatic failure, isolated acute hemolysis, to psychiatric illness [McCullough et al 1983;Steindl et al 1997]. Wilson disease is caused by mutations in the gene that encodes the copper-transporting ATPase ATP7B [Burkhead et al 2010]. This mutation prevents copper transport into the Golgi complex and binding of copper to apoceruloplasmin.…”
Section: Wilson Diseasementioning
confidence: 99%